Neurobiologia das reações de defesa: avaliação celular e comportamental de camundongos submetidos ao teste de exposição ao rato - Queiroz, Rafaella Misael (2017)
Brain areas, such as amygdala (AMY) and periaqueductal gray (PAG), are important structures of the aversive brain system responsible for mediating defense reactions in animals against aversive stimuli. Therefore, the objective of this study was to evaluate the neuronal activation of the AMY and PAG brain area, as well as the importance of inactivation of PAG and the action of neurotransmitter corticotrophin releasing factor (CRF) and the intracellular protein kinase A (PKA) pathway in the behavioral responses of male Swiss mice (30-40g; Ethics Committee: n ° 100/14/UFU) exposed to the Rat Exposure Test (RET). To assess the cellular response with in AMY and PAG, we have checked for changes in Fos protein expression, an important indicator of neuronal activity. For this, the animals were submitted to RET for 10 minutes, exposed to their predator rat (alive) or toy rat (plush rat) for once (acute) or five (interleaved days, repeated), while the control group was not exposed. After test, animals were sacrificed and its brains processed by immunohistochemistry for Fos based on the protocol developed by the Laboratory of Neurosciences and Behavior-UNIFESP. The number of Fos-positive cells was evaluated in ImageJ software and expressed as mean ± SEM, being significant when p < 0.05. To evaluate the behavioral responses, guideline cannula were implanted into the PAG of the mice and microinjections of vehicle (Salina) or drugs were carried out according to experiment. Experiment 1, muscimol (agonist GABA A; dose: 0.06nmol) + baclofen (GABA B agonist; dose: 0.6nmol), MB; experiment 2, H89 (PKA inhibitor, doses: 2.5nmol or 5.0nmol) and experiment 3, CP 376395 (CRF1 antagonist; doses: 1.5nmol or 3.0nmol) and exposed to RET for 10minutes. Tests were recorded, behaviors evaluated and expressed as mean ± SEM, considering significant when p < 0.05. Results did not indicate any significant difference of Fos-positive intra AMY. However, mice exhibited higher numbers of cells expressing Fos intra PAG when compared to the toy and control groups, both in the acute and repeated tests. In addition, when compared to each other, repeated exposure induced greater Fos expression than acute exposure indicating a possible difference in PAG modulation against repeated and acute stress. Behavioral analysis indicated that the mice exposed to the rat showed a tendency to the significance in the reduction of the time spent in the most aversive area of the RET (surface, unprotected area), significant less time climbing and contact with wire mesh screen in a group of repeated exposures and a strong tendency to decrease contact in a single exposure group (p = 0.07). Frequency and time of stretched attend posture were also altered or strongly tended to be altered (p = 0.06) when we compared exposure to the rat or toy rat. Intra PAG mouse treatment with MB increased the time spent on the most aversive area of the apparatus and decreased or tended to decrease the display of risk assessment behaviors. We also verified that microinjection of CP intra PAG of mice promoted anxiolytic-like effect, since there was an increase in the time spent of the animals in the unprotected area of the RET (dose: 1.5 nmol), an effect also observed with treatment with H89, at the dose of 5,0 nmol. Therefore, results suggest an involvement of the PAG, the CRF neurotransmitter and the PKA pathway in the modulation of the defensive responses in mice exposed to the RET. In addition, there seems to be a difference in the modulation of repeated and acute stress, since repeated exposure induced greater neuronal activation within PAG.